MAKING GOAT HERDERS AS SCAPE GOATS FOR HIGH-ALTITUDE PASTURE DEGRADATION: A CASE STUDY OF HARIPUR-NARAN PASTORAL SYSTEM IN NORTHERN PAKISTAN - W. Rashid; I. Rahim; M. Nafees; S. A. U. Rehman; M. Khurshid; J. Shi (Journal of Animal and Plant Sciences, 2019)
This study identified and explored the changes in traditional trekking routes of pastoral communities between upland and lowland pastures. Data about trekking routes were collected by field surveys through constant trekking accompanying the herders and participatory meetings.  Results show that landless herders resonated between lowland and upland pastures by moving along approximately 220 km long corridors seasonally. They were travelling through mountain trekking routes (Timbri-Kund Bangla and Makra-Gatti Galli) and road-based route to reach their seasonal pastures. Around 43% of the herders followed the Timbri-Kund Bangla route (TKB route) with 20 resting places, 41% herders followed the road-based route with 28 resting places, and 16 % herders followed Ghari-Makra-Gatti Galli route (GMGG route) with 26 resting places. Although there were more resting places on the road-based route, only about half of the resting places on this route were actually availed during mobility. Thus, time spent on the road-based route (20-25 days) was significantly less than on the mountain routes. Significantly less time (on average 1.72 days) was spent at each resting place along the road-based route. The early arrival and late departure of the herds at the upland pastures caused pasture degradation due to their consumption of vegetation which was still washy and not suitable for grazing then. The study concludes that closure of resting places and trekking routes is the main cause for changes in mobility patterns. Reopening resting places and trekking routes, accompanied by provision of veterinary care, mobile education and grazing rights, is recommended to safeguard this economical and environment-friendly traditional transhumance system.
Keywords: Trekking routes; Mobility; Transhumance Corridors; Hindrances; Transhumance